1999
DOI: 10.1136/gut.45.6.840
|View full text |Cite
|
Sign up to set email alerts
|

Wheat bran affects the site of fermentation of resistant starch and luminal indexes related to colon cancer risk: a study in pigs

Abstract: Background-Recent studies suggest that resistant starch (eVective in producing butyrate and lowering possibly toxic ammonia) is rapidly fermented in the proximal colon; the distal colon especially would, however, benefit from these properties of resistant starch. Aims-To determine whether wheat bran (a rich source of insoluble non-starch polysaccharides), known to hasten gastrointestinal transit, could carry resistant starch through to the distal colon and thus shift its site of fermentation. Methods-Twenty fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
114
1
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(122 citation statements)
references
References 35 publications
6
114
1
1
Order By: Relevance
“…In this study, whole cecum weights in the HAS-administered groups increased significantly ( Table 2), suggesting that HAS reached the cecum without digestion. It has been reported that starch that reaches the large intestine is fermented by intestinal bacteria, resulting in increases in butyrate concentration in the large intestine in humans (10), pigs (16) and rats (24).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, whole cecum weights in the HAS-administered groups increased significantly ( Table 2), suggesting that HAS reached the cecum without digestion. It has been reported that starch that reaches the large intestine is fermented by intestinal bacteria, resulting in increases in butyrate concentration in the large intestine in humans (10), pigs (16) and rats (24).…”
Section: Discussionmentioning
confidence: 99%
“…Other diseases related to changes in the composition and activity of the intestinal microbiota include diarrhoea and necrotising enterocolitis (NEC) (4,5) . As diet composition reflects the substrates available for the intestinal microbiota, thereby affecting their composition and metabolic activity, dietary modulation appears to be a valuable and promising tool to improve host health by beneficially steering microbial composition and metabolism (6,7) . Therefore, dietary supplementation of food additives, such as probiotics, has been frequently proposed.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, addition of wheat bran to the inocula resulted in raised SCFA concentrations after the 12-h incubation (P < 0.001, Table 2). The caecal and colon SCFA production was elevated also in pigs fed diets containing wheat bran as a fibre supplementation (Govers et al 1999;Molist et al 2009). …”
Section: Resultsmentioning
confidence: 99%